2020
DOI: 10.3390/jcm9123962
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Evidence Related to COVID-19 in Patients with Diabetes Mellitus

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has rapidly evolved into a global pandemic. The hyperglycemia in patients with diabetes mellitus (DM) substantially compromises their innate immune system. SARS-CoV-2 uses human angiotensin-converting enzyme 2 (ACE2) receptors to enter the affected cell. Uncontrolled hyperglycemia-induced glycosylation of ACE2 and the S protein of SARS-CoV-2 could facilitate the binding of S protein to ACE2, enabling vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 82 publications
1
18
0
2
Order By: Relevance
“…We also found that the proportions of patients with residual lung abnormalities were significantly higher in the group with diabetes or hyperglycemia than in the control group. Previously, individuals with diabetes or secondary hyperglycemia were shown to be at a high risk of severe COVID-19 due to their impaired immunity and dysfunctional proinflammatory cytokine responses [7] , [27] . Thus, underlying comorbidities are associated with disease severity and, potentially, a slow recovery, which may also lead to a greater degree of residual pulmonary changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the proportions of patients with residual lung abnormalities were significantly higher in the group with diabetes or hyperglycemia than in the control group. Previously, individuals with diabetes or secondary hyperglycemia were shown to be at a high risk of severe COVID-19 due to their impaired immunity and dysfunctional proinflammatory cytokine responses [7] , [27] . Thus, underlying comorbidities are associated with disease severity and, potentially, a slow recovery, which may also lead to a greater degree of residual pulmonary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, severe acute respiratory syndrome coronavirus (SARS-CoV) has been shown to damage islet cells through its receptors and cause secondary hyperglycemia in patients who were not using any glucocorticoids and who did not have a prior history of diabetes [4] . Several recent studies have shown that hyperglycemia at admission and previously diagnosed diabetes are significant predictors of severe disease and mortality in COVID-19 patients [5] , [6] , [7] . Similar findings were previously observed in patients infected with SARS-CoV [8] and middle east respiratory syndrome coronavirus (MERS-CoV) [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Following interaction with SARS-CoV-2, virus-dependent ACE2 downregulation is responsible for the accumulation of ACE1-derived Ang II, which mediates the inflammatory response and parenchymal injury in lungs and other organs by interacting with AT1R and activating NF-κB. ACE2 glycosylation, as occurring under hyperglycemia conditions typical of diabetes, increases the binding affinity of ACE2 to the virus and favors the spreading of the virus to multiple organs [90]. Preventing imbalances in RAS members or favoring the activity of Mas receptor (MasR) or AT2R is a therapeutic strategy to restrain SARS-CoV-2-dependent tissue damage in COVID-19 patients [9].…”
Section: Rage and The Renin-angiotensin System Overlapping Pathways And Biased Signaling With Potential Relevance In Covid-19mentioning
confidence: 99%
“…A rise in glycosylated ACE-2, ADAM17 and TMPRSS2 expression in pancreatic islets and glycated SARS-CoV-2 S-protein in an individual with DM were observed. Thus, it is predicted that increased TMPRSS2 expression is linked to entry of the virus in humans[ 39 , 48 ]. The role of interferon-induced transmembrane proteins and ADAM17 was also investigated, and a possible association of their expression with SARS-CoV-2 infection and severity was suggested[ 39 , 48 ].…”
Section: Link Between Dm and Covid-19mentioning
confidence: 99%